Pourquoi (re)penser la communication de solidarité internationale ? - Florine Garlot (Communiquer)
This article stems from an action-research project. The aim is to identify the causes of the crisis in international solidarity communication. Our empirical work suggests two main causes. On the one hand, international solidarity communication seems to be dominated by transmissive and persuasive approaches (Dacheux, 1998; Quéré, 1991) that do not allow us to understand the complexity of the issues. On the other hand, the relationship of international solidarity seems to be embedded in a philanthropic dimension (Freyss, 2004; Laville, 2010), itself specific to colonial and universalist thinking (Glissant, 1997; Quijano, 1994). It is therefore important, as we shall do to conclude, to suggest proposals for another communication approach deeply rooted in the field of international and intercultural communication.